Sustainable housing: demographic analysis of customers’ demands in Klang Valley - N.E. Myeda,; S.N. Kamaruzzaman,; S.M. Zaid,; Fong, Y.P. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Construction industry in Malaysia has been creating thousands of opportunities boosted by a series of government policies during economic recession in 2008. Although construction sector contributed to economic growth, the resourced of this intensive sector also caused resource depletion, environmental pollutions and global warming. This has drawn for the need for sustainability development. Public are aware of the importance of sustainability due to environmentalists are frequently emphasising upon adverse impacts of development and urbanisation on our mother earth. This research aims to understand consumer’s perception, wiliness-to-pay and preferences in Klang Valley, Malaysia due to high intensity of GBI certified green buildings are located in the area. 294 valid responses were collected using structured questionnaire surveys distributing. Data collected were undergone descriptive analysis and correlation inferential analysis using statistical analysis software – SPSS Version 20. It was found that consumers with higher income level are more willing to pay extra cost incurred in obtaining green buildings. Most of the respondents preferred to have basic public amenities located within radius of 750m from house. They also prefer to own houses with better sound proof as well as greater greenscape area.